Digital Leadership Components of School Administrators Responding to Changes in the BANI World Era under Khon Kaen Primary Educational Service Area Office 5 - Thepphabat, Kittiphan; Piampuechana, Niyada (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were 1) to analyze the components of digital leadership of school administrators and 2) to analyze confirmatory factors of digital leadership of school administrators responding to changes in the BANI World era under Khon Kaen Primary Educational Service Area Office 5. This research was a descriptive research. The sample group consisted of school administrators and teachers under Khon Kaen Primary Educational Service Area Office 5, with the total number of 500 people, using stratified random sampling method. The research instrument was a 5-level rating scale questionnaire with content validity of 0.67-1 and questionnaire reliability of 0.960, and semi-structured interview. The statistics used in data analysis comprised frequency, percentage, mean, standard deviation, exploratory factor analysis, and confirmatory factor analysis. The research results were found that: 1. The results of exploratory component analysis of digital leadership of school administrators responding to changes in the BANI World era were found that, in order of the component weights, they were as follows: 1) Having a digital vision, with a weight between 0.918-0.942. 2) Creating a learning culture in the digital world era, weights range between 0.890 - 0.921. 3) Excellent professional practices, with a weight between 0.897 - 0.930. 4) Creating a digital learning culture network, with a weight between 0.898 - 0.928. 2. The results of confirmatory factor analysis of digital leadership of school administrators responding to changes in the BANI World era were found that the measurement model was consistent with the empirical data. The level of consistency was equal to 46.104, P-value was equal to 0.1450, with no statistical significance, SRMR value was equal to 0.014, RMSEA value was equal to 0.022, CFI value was equal to = 0.998 and TLI value was equal to 0.997. The weight value in all aspects of components was positive between 0.880-0.999 with statistical significance at .01 level for all values.